2014
DOI: 10.1007/s40629-014-0011-7
|View full text |Cite
|
Sign up to set email alerts
|

Rupatadine: efficacy and safety of a non-sedating antihistamine with PAF-antagonist effects

Abstract: SummaryRupatadine is a modern non-sedating H1-antihistamine that also haswith additional antagonist effects on platelet-activating factor (PAF). Under the tradenames Rupafin® and Urtimed®, Rrupatadine is approvedregistered in Germany for the treatment of allergic rhinitis and urticaria infor adults and children aged over 12 years. In this review, the available literature available to date onregarding the pharmacological profile and clinical application of Rrupatadine is reviewed and compared to other conventio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
54
0
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 42 publications
2
54
0
8
Order By: Relevance
“…The pharmacokinetic profile of rupatadine and its main metabolites in healthy Japanese subjects, also assessed in this clinical trial, has been recently reported by Taubel et al . The PK parameters in Japanese subjects were shown to be in close agreement with the results exhibited by several white Caucasian studies …”
Section: Discussionsupporting
confidence: 81%
See 4 more Smart Citations
“…The pharmacokinetic profile of rupatadine and its main metabolites in healthy Japanese subjects, also assessed in this clinical trial, has been recently reported by Taubel et al . The PK parameters in Japanese subjects were shown to be in close agreement with the results exhibited by several white Caucasian studies …”
Section: Discussionsupporting
confidence: 81%
“…Recently Rupafin in tablet form and as pediatric oral solution have also been approved by Health Canada. As part of rupatadine's drug development program, its safety has been extensively investigated in several nonclinical and clinical studies …”
mentioning
confidence: 99%
See 3 more Smart Citations